Public health messages during a global emergency through an online community: a discourse and sentiment analysis - Watkins, Megan; Mallion, Jaimee S.; Frings, Daniel; Wills, Jane; Sykes, Susie; Whittaker, Andrew (Frontiers in Digital Health, 2023)
Social media’s growing popularity and presence in our lives brings associated risks such as the spread of mis- and dis-information, particularly when these may be unregulated in times of global crisis. Online communities are able to provide support through enabling connection to others and provide great potential for dynamic interaction and timely dissemination of information compared to more traditional methods. This study evaluates interactions within the Essex Coronavirus Action/Support Facebook private group, which set out to prevent the spread of COVID-19 infection by informing Essex residents of guidance and helping vulnerable individuals. At the outset, 18 community administrators oversaw the group which attracted approximately 37,900 members. Longitudinal Facebook group interactions across five periods spanning the UK lockdowns 2020-2021 were analysed using psychological discourse analysis and supplementary computed mediated analysis to further explore sentiment and linguistic features. Findings endorsed that the group provided a protected space for residents to express their feelings in times of crisis and an opportunity to address confusion and concern. The effective communication of public health messages was facilitated through promoting desired interaction and the construction of group identities. Administrators worked with group members to achieve a shared understanding of others’ perspectives and the COVID-19 evidence base which led to mobilisation of the provision of support in the community. This was accomplished through the application of rhetorical and interactional devices. The study demonstrates how online groups can employ discursive strategies to engage audiences, build cohesion, provide support and encourage health protective behaviours. This has implications for public health teams considering designing, implementing or evaluating such interventions.